Patriotyzm jako wartość w serialu telewizyjnym na przykładzie Czasu honoru. Powstanie - Molicka, Paulina (Dydaktyka Polonistyczna, 2018)
This article is devoted to the issue of valuation in a television series. The exemplification material comes from the popular Polish production Czas honoru. Powstanie. The text aims to present representative examples – mainly the attitudes of young people who can be a model for modern generations of Poles.